Winterbach’s Spyt and Scholtz’s production: An expression of a postmodern impasse - Lida Krüger (Tydskrif vir Letterkunde, 2020)
Some scholars have declared metamodernism to be postmodernism’s successor, and Afrikaans novelist Ingrid Winterbach’s work has been argued to be an example of this distinct move away from the postmodern paradigm. However, in this article I present the alternative interpretation that Winterbach’s play, Spyt (Regret), rather represents postmodernism’s inability to give way to its successor. An investigation from a postmodern perspective leads me to conclude that, in both the text and performance of this play (directed by Brink Scholtz), an escape from the postmodern paradigm entails the end of all representation. Winterbach reduces all of the characters’ endeavours to surfaces which become parodies. All their experiences are commodified and any attempt at uncovering a deeper meaning to life is undermined by ridicule. Winterbach furthermore draws attention to some of her characters’ limited vocabulary and reliance on English loanwords. This culminates in a powerful scene where the loanword ‘awesome’ is repeated to the extent that it becomes simultaneously meaningless and indispensable; a tension that she does not resolve. In addition, the crossing of the boundary between life and death, which has been described as postmodernism’s final frontier, is portrayed by relying on an obsolete narrative. The play therefore suggests a postmodern impasse, rather than a move towards a new paradigm. an a move towards a new paradigm.